The Effective Factors in the Accuracy of Intraoral Scanners: A Systematic Review - sayed shojaedin shayegh; Maryam Jahangiri (Mashhad University of Medical Sciences, 2024)
Background: The use of digital technology and intraoral scanners in dentistry has gained increasing popularity. Various factors can impact intraoral scanning accuracy and gaining competent knowledge of these factors can enhance the accuracy, speed and quality of intraoral scanning procedures. In this study, we aimed to investigate the factors influencing the accuracy of digital impressions recorded by intraoral scanners.Methods and Materials: The present systematic review was performed according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020. A comprehensive search was conducted across databases such as PubMed, Google Scholar, Scopus, Science Direct, Web of Science and Cochrane Library using terms related to "intraoral scanner", "CAD/CAM", "digital impression", "digital dentistry" and "accuracy". Studies that were published from January 2015-February 2024 in English or Persian language, were retrieved.Results: A total of 1460 studies were initially identified and 100 studies were screened by title and abstract. Case report studies or those which were non-relevant to our PICO model were excluded. Finally, the full text of 30 studies were reviewed.Conclusion: Multiple influencing factors were identified. These factors were classified into five main categories that were either related to the operator (expertise and employed scanning strategy), utilized scanner (size and type), scanned tooth (preparation, distance from adjacent teeth and topographic characteristics), implant (implant location, angulation and scan body), jaw (jaw deformities, intra-arch distance and partial or complete edentulism) or ambient conditions (ambient light and temperature).